The implementation of international law in the Irish legal system : the effect of European Union membership - Fennelly, David (Trinity College (Dublin, Ireland). School of Law, 2011)
As the competence of the European Union (EU) in the field of international relations has expanded, the role of the EU in the implementation of international obligations has correspondingly increased. This thesis examines the effect of this evolving EU role on the implementation of international law in the Irish legal system. The method adopted for conducting this examination draws reference from the principal sources of international law. To this end, four main sources are identified: international agreements; customary international law; acts of international organisations (taking the specific case of United Nations Security Council resolutions); and international judicial decisions. Before examining the implementation of each of these sources, in order to provide the necessary context for the study. Chapter 1 sets out the theoretical and international law frameworks of that process and Chapter 2 examines the changing legal framework governing the conduct of international relations in Ireland as a result of the growing role of the EU. In the context of examining the effect of EU membership on the implementation of each of these sources, four steps are undertaken in the individual chapters: first, an introduction to the source in question and the issues arising in its implementation within internal legal systems; secondly, an analysis of the Irish position independently of the EU; thirdly, an analysis of the EU position; fourthly, a conclusion which aims to synthesise the effect of the EU position on the Irish position. The substance of these chapters examines the relevant legal rules, whether they be based in treaty, constitution, statute or case-law. While the amount of literature on many of these issues from an Irish perspective is very limited, thus necessitating a more elaborate articulation of the Irish position, the amount of literature on these issues from an EU perspective is significant.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin